Studi Deskriptif Pembuatan Karya Seni Finger painting Pada Pembelajaran Seni Budaya Kelas IB Sekolah Dasar - Fristina, Candeni Bunga; Tarmizi, Pebrian; Susanti, Atika (JURIDIKDAS, 2025)
This research aims to describe the process of making finger painting works of art and the results of finger painting works as fine art works. This type of research is qualitative research with descriptive methods. The research subjects were class I B students at SD Negeri 02 Bengkulu City. The instruments in this research were the researchers themselves using observation, interviews and documentation. The data collection techniques used were observation, interviews and documentation. Data analysis is carried out by collecting data, reducing data, presenting data and drawing conclusions. This research data validity technique uses triangulation and member checking. The results of this research: (1) The process of creating a work is carried out in 4 stages, namely preparing tools and materials, the stage of providing material on basic finger painting techniques, the stage of preparing sketches, and the stage of painting using your fingers. The work created is in the form of finger painting. When preparing the materials and tools, neither the teacher nor the students experience any difficulties. Next, in the stage of explaining the basic techniques of Finger painting, all groups had no difficulty. The final stage was painting the picture, group 3 experienced difficulty. (2) The students' work is described based on the elements of fine art which include the elements of spots, lines, colors, textures and light and darkness as well as the principles of fine arts which include the principles of unity, balance, rhythm, emphasis, proportion and harmony. Thus, it can be concluded that all the work of class I B students at SD Negeri 02 Bengkulu City has been made using basic Finger painting techniques and the work created contains elements and principles of fine art. However, the principle of proportion is still less visible in his work.